„Rosja śniegiem stoi”. Motyw śniegu/lodu w twórczości Władimira Sorokina - Zywert, Aleksandra (Rusycystyczne Studia Literaturoznawcze, 2015)
The theme of snow/ice, as one of the emblems of Russia, prevails in the works of Vladimir Sorokin virtually as a constant. Depending on the period and direction of the author’s artistic explorations, it acquires different meanings. Initially, it facilitates the deconstruction of classical discourse, but gradually it transforms into a symbol of power founded on violence to eventually become an inextricable part of the metaphor of Russia’s imminent death.